Comparison of three definitions of metabolic syndrome and relation to risk of recurrent preeclampsia. (2nd January 2021) - Stekkinger, Eva; Scholten, Ralph R.; Heidema, Wieteke M.; Spaanderman, Marc E.A.
ABSTRACT: Objective. To determine the prevalence of metabolic syndrome in formerly preeclamptic women according to three definitions of metabolic syndrome (World Health Organization [WHO], International Diabetes Federation [IDF], and Third Adult Treatment Panel updated [ATPIII]), to evaluate agreement amongst definitions and to compare the risk of recurrent preeclampsia. Methods. In 197 women with a history of preeclampsia, we determined presence of metabolic syndrome using WHO, IDF, and ATPIII criteria. We evaluated agreement amongst definitions by using Kappa statistics. The prevalence of recurrent preeclampsia was compared between women with and without inter-pregnancy metabolic syndrome, according to the three definitions. Results. A total of 40 (20%), 46 (23%), and 31 (16%) of women with previous preeclampsia were classified as having metabolic syndrome postpartum according to WHO, IDF, and ATPIII criteria, respectively. Agreement among criteria was considered substantial between WHO and IDF ( κ = 0.64, 95% CI 0.53–0.79), WHO and ATPIII ( κ = 0.74, 95% CI 0.62–0.86), and IDF and ATPIII ( κ = 0.66, 95% CI 0.51–0.77). The prevalence of recurrent preeclampsia was 45% versus 17% in women with and without inter-pregnancy metabolic syndrome according to the WHO definition ( P < 0.001), 26% versus 21% according to the IDF criteria (P = 0.16), and 39% versus 20% according to the ATPIII definition (P = 0.02). Conclusions. Agreement among WHO, IDF, and ATPIII criteria of metabolic syndrome in women after preeclampsia is considered substantial. The risk of recurrent preeclampsia is almost one out of two in women with inter-pregnancy metabolic syndrome according to the WHO criteria.